2007
DOI: 10.1002/ange.200704007
|View full text |Cite
|
Sign up to set email alerts
|

Rediscovering Pasteur's Quasiracemates

Abstract: Neu aufgerollt: Durch Wiederholung eines von Pasteur 1853 beschriebenen Experiments gelang es, zwei kristalline Phasen als Ammonium‐(+)‐hydrogentartrat (Mittelteil der gezeigten Kristalle) und quasiracemisches Ammonium‐(+)‐hydrogentartrat/(−)‐hydrogenmalat (Stirnseiten der Kristalle) zu identifizieren. Das Quasiracemat besteht aus annähernd inversionssymmetrischen Molekülanordnungen, in denen die Hydrogentartrat‐ und Hydrogenmalat‐Komponenten ein homomeres Catemermotiv bilden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Quasi-racemate crystals of small organic molecules were first described by Pasteur in 1853, [32] and their properties have more recently been explored by Curran [33] and Wheeler. [34] The quasi enantiomers that were used to form these crystals are related to each other by an almost mirror-image relationship and can be converted to the true enantiomers by slightly changing the chemical composition of one or more atoms or functional groups. Although small-molecule quasi-racemates are widely used in asymmetric organic synthesis and for organizing supramolecular arrays, utilization of macromolecular quasi-racemates was demonstrated only recently when we found that the incorporation of an additional -Se-CH 2 -in only the l enantiomer of snowflea antifreeze protein still facilitated crystallization with the d-protein molecule as was seen for the true racemate.…”
mentioning
confidence: 99%
“…Quasi-racemate crystals of small organic molecules were first described by Pasteur in 1853, [32] and their properties have more recently been explored by Curran [33] and Wheeler. [34] The quasi enantiomers that were used to form these crystals are related to each other by an almost mirror-image relationship and can be converted to the true enantiomers by slightly changing the chemical composition of one or more atoms or functional groups. Although small-molecule quasi-racemates are widely used in asymmetric organic synthesis and for organizing supramolecular arrays, utilization of macromolecular quasi-racemates was demonstrated only recently when we found that the incorporation of an additional -Se-CH 2 -in only the l enantiomer of snowflea antifreeze protein still facilitated crystallization with the d-protein molecule as was seen for the true racemate.…”
mentioning
confidence: 99%
“…The advantages of removing the requirement that molecules be related by rotations of 2/n, n = 1, 2, 3 or 6, are more important than the disadvantages of raising the number of different intermolecular contacts. The experiments of Wheeler with carboxylic acids and amides (Wheeler et al, 2008;Breen et al, 2008;Lineberry et al, 2008, and references therein), and those of Gö rbitz with amino acids (Dalhus & Gö rbitz, 1999a,b,c, 2000Gö rbitz et al, 2009) suggest that single crystals of quasiracemates are not difficult to grow, at least as long as the constituent molecules form good hydrogen bonds. Some inorganic examples have been characterized by Englert (Englert et al, 2002;Calmuschi et al, 2004, and references therein).…”
Section: The Existence Of Quasiracematesmentioning
confidence: 99%
“…L ‐malic acid ( L ‐ 4 ) differs from L ‐tartaric acid ( L ‐ 2 ) by the lack of one hydroxy group and by the absolute configuration of its only stereogenic center. The two acids are thus quasi‐enantiomers and their successful combination in quasi‐racemic crystals was demonstrated by Pasteur long ago9a and recently fully characterized 9b. We thus endeavored to crystallize both acids in complex with 3 .…”
mentioning
confidence: 98%
“…As observed in solution, 4 ‐ l exists in two disordered positions in the solid state, arising from its dissymmetric structure. This disorder relates to the disorder of malic acid in its quasi‐racemic crystals with tartaric acid 9b…”
mentioning
confidence: 99%